Comparison of mechanical behavior of slabs reinforced with GFRP and steel - Christ, Roberto; Ehrenbring, Hinoel Z.; Pacheco, Fernanda; Schneider, Diego; Tutikian, Bernardo F.; Moreira, Gian de Fraga; Wegher, Leandro; Beliaev, Oleg (Revista ALCONPAT, 2024)
The objective of this study is to evaluate the mechanical behavior of GRFP in massive concrete slabs. The use of glass fiber reinforced polymer (GFRP) rebars in construction design has been an alternative technique to provide more durable structures. However, there is a need to evaluate the behavior of GFRP reinforced slabs under flexure and to compare the service state (SS) and ultimate service state (USS) of the loaded element. Thus, reinforced concrete slabs of varying thicknesses were constructed with steel and GFRP rebars. Results show that the applied load for maximum span deflection of the GFRP slab under SS was 50% lower than for the one with steel reinforcement. The maximum span deflection of the GFRP slab under USS was also 282% larger than for steel rebars reinforcement.